Tempol Attenuates Neuropathic Pain by Inhibiting Nitric Oxide Production - Donglin Jia; Huan Wang; Bin Han; Liping Zhang; Jianrong Guo (Analytical Cellular Pathology)
Background. Neuropathic pain not only affects individual life quality but also increases economic burden for the society. Treatment to alleviate neuropathic pain is required. Methodology. Fifty rats were randomly assigned into sham, spinal nerve ligation, and three treatment groups with different doses of Tempol (100, 200, and 300 mg/kg, respectively), with 10 rats in each group. A neuropathic pain model was created with spinal nerve L5 and L6 ligation. Mechanical allodynia and thermal hyperalgesia were tested preoperatively (day 0) and postoperatively (days 1, 3, 5, and 7). Spinal cord levels of nitric oxide, as well as activities of nitric oxide synthase and acetylcholinesterase, were tested in postoperative day 7. Results. Compared with rats in the spinal nerve ligation group, rats in Tempol treatment groups had decreased responses to mechanical pain and cold plate stimulations. A high dose of Tempol produced more attenuating effects. The level of nitric oxide and activity of nitric oxide synthase were also decreased with Tempol treatments, whereas no significant changes were observed in the activity of acetylcholinesterase. Conclusions. Tempol attenuated an experimental rat model with neuropathic pain by inhibiting nitric oxide production.